Keanekaragaman Teripang (Holothuroidea) di Perairan Bagian Timur Pantai Natuna Kepulauan Riau - Sukmiwati, Mery; Salmah, Siti; Ibrahim, Sanusi; Handayani, Dian; Purwati, Pradina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
This study was aimed to investigate diversity of sea cucumber. Samples were collected in the coastal waters of Natuna, Riau Islands in June 2009. Samples were taken from 2 locations: Sepempang and Pengadah beach. Sampling was done by using a transect quadrant of 5x5 m. This sampling and observation on its microhabitat were conducted by snorkeling. Analyses on the sea cucumber community structure were based on its diversity, equitability, density and frequency of occurance. The result showed that at both locations there are 16 species from two families: Holothuriidae and Stichopodidae. The higher diversity index (H) was 3.256 and equitability index (e) was 0.993. The higher density of species were 0.0032 ind/m2. The higher frequency of occurance was 27.71% by H. atra.